2016
DOI: 10.1521/soco.2016.34.6.504
|View full text |Cite
|
Sign up to set email alerts
|

News Media Depictions of Obama Influence Automatic Attitudes: Implications for the Obama Effect

Abstract: Positive media depictions of Obama likely contribute to the so-called "Obama effect." However, like any attitude-object, effects of those depictions can depend on contextually positive or negative portrayals. We hypothesized that politically conservative news web sites (e.g., FoxNews.com) visually depict Obama more negatively than moderate sites (e.g., CNN. com), and that incidental exposure to such dissimilar depictions can differentially impact perceivers' attitudes toward Obama, particularly when pre-existi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(72 reference statements)
1
1
0
Order By: Relevance
“…Results indicated that participants with weaker attitudes developed more negative associations with Obama when repeatedly exposed to his portrayal in a negative manner. [202] Broadly speaking, this work aligns with Columb and Plant (2016) in concluding that while attitude change may be the result of counterstereotypical exemplars, it appeared that "exemplar valence may be the primary cause of the effect." [202] Implicit Attitude Formation Studying the processes behind how individuals form implicit attitudes, Hu, Gawronski, and Balas evaluated two competing theories on the process of evaluative conditioning.…”
Section: Childrensupporting
confidence: 64%
See 1 more Smart Citation
“…Results indicated that participants with weaker attitudes developed more negative associations with Obama when repeatedly exposed to his portrayal in a negative manner. [202] Broadly speaking, this work aligns with Columb and Plant (2016) in concluding that while attitude change may be the result of counterstereotypical exemplars, it appeared that "exemplar valence may be the primary cause of the effect." [202] Implicit Attitude Formation Studying the processes behind how individuals form implicit attitudes, Hu, Gawronski, and Balas evaluated two competing theories on the process of evaluative conditioning.…”
Section: Childrensupporting
confidence: 64%
“…The first study revealed that undergraduate participants found the news websites' images of Obama varied systematically, as images from FoxNews.com -regardless of whether text accompanied the image-yielded more negative portrayal ratings than CNN.com. [202] A second study used a Single Category IAT (SC-IAT) to assess undergraduate participants' automatic attitudes toward Obama, as well as other measures. Results indicated that participants with weaker attitudes developed more negative associations with Obama when repeatedly exposed to his portrayal in a negative manner.…”
Section: Childrenmentioning
confidence: 99%